Financial Stability of Banks and Its Monitoring in Ukraine (Economics and region, 2020)
The concept of financial stability of banks as a complex and multifaceted category, the content of which is constantly enriched, has been developed. Approaches to determining the financial stability and financial stability of banks, in particular, are considered. It is noted that modern operational, functional, institutional, technological features of banks cannot but affect the content of their financial stability and update the mechanisms for its ensuring. Emphasis is placed on the need for early adaptation of banking institutions to objective transformations of the economic environment through the integration of risk-oriented approach and the use of advanced methods of bank management in all its business processes. The level of financial stability of banks in Ukraine is monitored, for which the main volume indicators of their activity and the Bank Z-score indicator calculated by the World Bank are analyzed. The analysis of indicators of banks’ penetration into the economy shows that the development of the banking sector lags behind the needs of the real sector, so its financial stability is relative, although there are trends to strengthen it. The constant increase in the capital base of Ukrainian banks and their compliance with capital adequacy ratios is particularly positive. However, the quality of banks’ loan portfolios is unsatisfactory, which poses a threat to their financial stability, even given the large amounts of formed provisions for loan impairment. The dynamics of financial stability indicators calculated by the National Bank of Ukraine confirms the existence of prerequisites for its long-term provision, despite the difficult environmental conditions. The directions of monitoring of financial stability offered in the article allow diagnosing its deterioration in time to prevent critical consequences for the national economy.
Keywords: bank; financial stability; equilibrium; adaptation; monitoring; capital adequacy; loan portfolio quality